A Novel Non-invasive Marker for Predicting Mechanical Prosthetic Heart Valve Thrombosis: Red Cell Distribution Width to Platelet Ratio - Çağatay Tunca MD; Mehmet Taha Özkan MD; Hatice Feyza Dilek MD; Murat Akdoğan MD; Ahmet Kıvrak MD; Kamuran Kalkan MD; Veysel Ozan Tanık MD; Bülent Özlek MD (Clinical and Applied Thrombosis/Hemostasis)
Background Prosthetic heart valve thrombosis (PHVT) is a serious and potentially life-threatening complication that affects patients with mechanical heart valves. Timely and precise prediction of PHVT is essential for prompt intervention. This study aims to assess the association between the ratio of red blood cell distribution width (RDW) and platelet (PLT) count with PHVT. Methods We conducted a retrospective analysis of 297 transesophageal echocardiography examinations performed between January 2007 and October 2022 on patients with mechanical mitral prosthetic valves. This cohort included 161 patients diagnosed with PHVT and 136 patients with functional prosthetic valves. Results Patients with PHVT were, on average, older than those with normofunctional valves (56 vs 53 years, p  = .046). Univariable analysis indicated that advanced age, heart failure (HF), chronic renal failure, COPD, reduced LVEF, ineffective anticoagulation, elevated D-dimer levels, and an elevated RDW-to-PLT ratio were associated with PHVT. The multivariable logistic regression analysis identified elevated RDW-to-PLT ratio (OR: 1.278, 95% CI: 1.142-1.327, p  = .001), ineffective anticoagulation, HF, and D-dimer were independently associated with PHVT. The ROC curve analysis demonstrated that the RDW-to-PLT ratio exhibited moderate diagnostic performance, with a cut-off value of 0.065, sensitivity of 65%, and specificity of 66%. Conclusion This is the first study demonstrating that the higher RDW-to-PLT ratio is associated with PHVT. Further studies are necessary to validate these findings in broader clinical settings.